Identification of Potential Plants Producing Tannin-protein Complex for a-amylase as Botanical Pesticide - Asriyah Firdausi; Tri Agus Siswoyo; Soekadar Wiryadiputra (Indonesian Coffee and Cocoa Research Institute, 2013)
Research on the development of botanical pesticides should be developed through new methods, such as by inhibiting the activity of digestive enzymes by secondary metabolites. The aim of this study was to identify some of potential plants as a source of tannin-protein complexes to inhibitthe activity of - amylase. The study of identification of potential plants producing the active ingredient tannin-protein complex was divided into three stages, 1) identification of potential plants producing tannin, 2) isolation of tannin-protein complexes, and 3) in vitro test of tannin-protein complexes effect of the -amylase activity. Some of the observed plants were sidaguri leaf (Sida rhombifolia), melinjo leaf (Gnetum gnemon), gamal leaf (Gliricidia sepium),lamtoro leaf (Leucaena leucocephala) , betel nut (Areca catechu) , and crude gambier (Uncaria gambir) a s a source of tannins and melinjo seed was used asprotein source. Betel nut and melinjo seed were the best source of tannin-protein complex, tannin content 1.77 mg TAE/mL with antioxidant activity of 90%,the ability to inhibit the activity of -amylase by 95% with IC 50 values of 10 mg/mL.Key words: Tannin, protein, -amylase, botanical pesticides,Areca catechu, Gnetum gnemon.